ANALYSIS OF THE IMPLEMENTATION OF THE DIGITAL ECONOMY AND ITS IMPACT ON PROFIT EARNINGS OF BERKAH DELIVERY MSMEs - Evi Dwi Kartikasari; Siti Afiqah Zainuddin; Amira Jamil, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
The growth of a region can be seen through its economic growth. The Lamongan economy of Indonesia, based on the amount of Gross Regional Domestic Product based on current prices in 2022 reached Rp 45.44 trillion and based on constant prices in 2010 reached Rp 29.45 trillion. Lamongan's economy in 2022 experienced an accelerated growth of 5.56% after previously growing in 2021 by 3.43%. In terms of production, the Transportation Business Field experienced the highest growth of 15.82%. The digital era gave rise to the phenomenon of the digital economy which later became a trend in the development of the business world. Berkah Delivery is a pioneering MSME in Lamongan engaged in transportation and goods delivery services. Its activities utilize economic digitalization ranging from marketing, online service methods, and payments. This study is intended to examine how implementing the digital economy is carried out and how it impacts profit generation by minimizing operational costs. This research was conducted qualitatively descriptively with case studies and using literature studies. The results of the research are expected to contribute to the right discourse and recommendations for MSME players who implement the digital economy system as a business revolution. The result of this research is that Berkah Delivery Lamongan has utilized the digital economy with its marketing mechanism through social media. The service system also uses an order system through wa and for payment using digital wallets or via transfer. However, the implementation of economic digitalization has not been fully in-depth because of the lack of digital literature. Financial management and payroll systems are still carried out manually, but in this case, it is shown that the operational costs incurred can be minimized because there is no need to provide physical space or operational maintenance of the building in its business.